Reproduction : a novel - Hall, Louisa, 1982- (Ecco, an imprint of HarperCollinsPublishers, 2023)
"A novelist attempts to write a book about Mary Shelley, author of Frankenstein, a mother and artist whose harrowing pregnancies reveal the cost of human reproduction. Soon, however, the novelist's own painful experiences of pregnancy and childbirth, as well as her increasing awareness of larger threats from climate change to pandemic, force her to give up on the book and turn instead to writing a contemporary Frankenstein, based on the story of an old friend who mysteriously reappears in her life"--